2021
DOI: 10.1186/s43044-021-00146-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of GRACE score for in-hospital and 6 months outcomes after non-ST elevation acute coronary syndrome

Abstract: Background The aim of this study was to determine the predictive value of the Global Registry of Acute Coronary Events (GRACE) score for predicting in-hospital and 6 months mortality after non-ST elevation acute coronary syndrome (NSTE-ACS). Results In this observational study, 300 patients with NSTE-ACS of age more than 30 years were included; 16 patients died during the hospital stay (5.3%). Of 284 patients at 6 months assessment, 10 patients die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…At present, the most commonly used clinical diagnosis methods are color Doppler ultrasound diagnosis, CT, MRI diagnosis, and blood index testing, among which color Doppler ultrasound diagnosis is the simplest and fastest diagnosis method. Blood index testing facilitates the determination of related diseases by evaluation of the expression level of specific blood indices, which is associated with more accurate diagnostic results [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most commonly used clinical diagnosis methods are color Doppler ultrasound diagnosis, CT, MRI diagnosis, and blood index testing, among which color Doppler ultrasound diagnosis is the simplest and fastest diagnosis method. Blood index testing facilitates the determination of related diseases by evaluation of the expression level of specific blood indices, which is associated with more accurate diagnostic results [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…11 A study by Kumar D et al, showed significantly higher 6-month mortality in the high-risk GRACE score compared to the intermediate-risk GRACE score, and only one patient with a low-risk GRACE score died at 6 months. 7 A retrospective study by Syyli N et al, showed that adding LVEF to GRACE score can significantly improve risk prediction of 6-month mortality after ACS. 12 The study also reported that both LVEF and GRACE score was significantly associated with 6-month mortality.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 GRACE score is not limited to any changes in the ST segment; hence it can be used for both STEMI and NSTEMI 6. …”
mentioning
confidence: 99%
“…The unmodifiable factors include age, gender, and family history while the modifiable factors are blood pressure, blood sugar level, cholesterol level, smoking, and obesity [5], [6], [7]. Recently, blood pressure has been recognized as a high-risk factor for ACS alongside high blood glucose (BG) level which aggravates the condition [6], hence, the presence of both conditions increases the risk of ACS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure is an important indicator for determining the prognosis of ACS and plays a huge role in the management of cardiovascular diseases [9]. Moreover, it is an element in the GRACE score used to determine patient mortality during hospitalization [8], [10]. Meanwhile, most studies show that low systolic blood pressure (SBP) is associated with mortality [9] while some show a contribution of hypertension to mortality in ACS patients [11].…”
Section: Introductionmentioning
confidence: 99%